Solitary Conjunctivocorneal Plasmacytoma Arising After Cataract Surgery. Issue 8 (August 2021) - Davidson, Max; Shah, Vallari; Shah, Chirag; Shahnazaryan, David; Jones, Sophie
Abstract : Purpose: To report a case of solitary plasmacytoma of the conjunctiva with corneal encroachment and to review the literature of all published cases. Methods: A 70-year-old man presented with 1-month history of pain and watering in the right eye, 7 months after undergoing cataract surgery in the same eye. Results: The mass was surgically excised. Pathology and immunohistochemistry were consistent with plasmacytoma. Staging studies found no evidence of systemic disease. Conclusions: To our knowledge, this is the first case of plasmacytoma in the literature to involve the cornea. This case was not associated with systemic disease. Surgical excision and brachytherapy remain options for cases without corneal involvement.